Revenue Administration : Compliance Risk Management; Overarching Framework to Drive Revenue Performance - Betts, Susan (Technical Notes and Manuals; Technical Notes and Manuals, 2022)
This technical note describes CRM at a high level and how tax administrations can implement a CRM framework to significantly strengthen revenue outcomes. A tax administration's primary role is to collect revenues on behalf of government to fund the country's social and economic goals. Taxpayers are expected to comply with their tax obligations as stated in the law. Compliance is the degree to which taxpayers meet their obligations, whether voluntarily or through efforts by the tax administration to enforce compliance. Using CRM allows a country to optimize its revenue collection by identifying and focusing resources on the highest risks to the tax base. While the concepts of CRM are transferable to the customs context, this note focuses on tax administration compliance risks.